Sucrose Permeability: A Simple Non-Invasive Marker of Gastro-Duodenal Damage in Dyspepsia - Saha, Tapan Kumar Saha Kumar; Bhattarai, Arabinda Mohan; Sharma, Manushree (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Diagnosis of gastro-duodenal mucosal damage usually requires endoscopy, an invasive procedure. An attempt has been made to assess the clinical validity of sucrose permeability test as a non-invasive marker of gastro-duodenal damage. Methods: The test was carried out in 65 patients of dyspepsia evaluated by endoscopy and 21 healthy controls. On endoscopy, gastro-duodenal epithelial damage was assessed in all patients of dyspepsia and grouped as: group 1 (normal gastro-duodenal mucosa, n=18), group 2 (Gastric ulcer, n=15), group 3 (Duodenal ulcer, n=10), group 4 (Gastritis, n=12) and group 5 (Duodenitis, n=10). Results: The mean urinary sucrose excretions (mg) in 5 hours after 100g oral load was found to be significantly higher in patients of gastric ulcers (183.6 ±169.7, p value < 0.001), duodenal ulcers (151.7± 79.2, p value <0.001), gastritis (115.6±59.2, p value <0.001) and duodenitis (105.2± 122.2, p value <0.05) as compared to controls (35.2±17.2). However, the mean sucrose excretion in patients of dyspepsia with normal endoscopic findings (42.5±14.8 mg) was almost similar to the control group (p value >0.05). A ROC curve analysis taking endoscopic findings as gold standard was undertaken to find the optimum cut-off to detect gastro-duodenal epithelial damage. Conclusions: The cut-off value of 64.5 mg/5h for urinary sucrose excretion provided the best sensitivity and specificity in the diagnosis of both surgical (gastric and duodenal ulcer) and non-surgical (gastritis and duodenitis) gastro-duodenal mucosal damage. At this cutoff sucrose permeability test provided a sensitivity of 72 % and specificity of 92%. Similarly, a cut-off value of 66.5 mg/5h of urinary sucrose excretion provided the best sensitivity and specificity in the diagnosis of surgical gastro-duodenal mucosal damage with sensitivity of 72% and specificity of 97%.